2021
DOI: 10.1016/j.clnesp.2021.03.020
|View full text |Cite
|
Sign up to set email alerts
|

The validity of the global leadership initiative on malnutrition criteria for diagnosing malnutrition in critically ill patients with COVID-19: A prospective cohort study

Abstract: Background and aim: We conducted the present study to investigate the nutritional status of critically ill COVID-19 patients and validate the GLIM criteria with respect to the SGA. Methods: In this prospective cohort study, 109 ICU patients were assessed for malnutrition based on GLIM and SGA criteria. The relation between nutrition assessment tools and duration of hospitalization and mortality were also evaluated. The sensitivity and specificity of GLIM criteria concerning the detection of malnutrition was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 23 publications
(25 reference statements)
6
46
1
7
Order By: Relevance
“…Yogurt, a fermented dairy product, exhibits interesting properties related to the presence of bioactive peptides and probiotics that may play a bene cial role in COVID-19 presentation and outcome. (Shahbazi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Yogurt, a fermented dairy product, exhibits interesting properties related to the presence of bioactive peptides and probiotics that may play a bene cial role in COVID-19 presentation and outcome. (Shahbazi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Patients who are critically ill are defined as cases with respiratory failure, shock, or multiorgan dysfunction, who should be treated in the intensive care unit (ICU) according to World Health Organization (WHO) classification ( 18 ). Some of the patients from our previous cohort study were included in the current study ( 19 ). The exclusion criteria comprised the patients without weight and height data, participation in other clinical trials, pregnancy, ICU stay <72 h, and those with end-stage kidney disease, cirrhosis, and cancer.…”
Section: Methodsmentioning
confidence: 99%
“…Up to 30% of infected patients present with an acute respiratory distress syndrome (ARDS) require urgent respiratory and hemodynamic support in the intensive care unit (ICU) (3). A highlighted feature in these catabolic patients with coronavirus disease 2019 (COVID- 19) is the cytokine storm that could result in muscle breakdown and proteolysis (4). In several previous studies on non-COVID critically ill, muscle breakdown was reported to be associated with worsened clinical outcomes (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Research is required now to apply the proposed GLIM criteria in validation studies for malnutrition diagnosis in diverse settings, diagnoses, sex and age groups (21) . Published work is now emerging with studies examining validation in different populations (22)(23)(24)(25)(26) and more developments are expected in the coming years.…”
Section: Screening Tools and Diagnostic Criteriamentioning
confidence: 99%